I have the initial value problem $4y''+4y'+4y = 1$; $y(0) = 3$, $y'(0) = 7$. I used undetermined coefficients to solve but got a very nasty answer. Is this the best method to use?

For the general solution I got $y(t)=e^{-x/2}(c_1cos(\frac {\sqrt{3}}{2}x)+c_2sin((\frac {\sqrt{3}}{2}x))$

The undetermined coefficient part was pretty easy -- basically just setting A=1/4 to get that the homogeneous equation plus 1/4.

Solving was trickier, I got $y(t)=e^{-x/2}(3cos(\frac {\sqrt{3}}{2}x)+\frac {17}{\sqrt3}sin((\frac {\sqrt{3}}{2}x))$

If something went wrong I would assume it was in solving for the coefficients.

  • $\begingroup$ It's best if you post your answer. If it looks very mathematical, then use this page: google.co.in/… for tips on how to write the answer. $\endgroup$ – астон вілла олоф мэллбэрг Dec 8 '16 at 3:10
  • $\begingroup$ @Moo Looks similar! Did you get the same general solution I did? Solving the initial value problem got very technical and may have been were we differed. $\endgroup$ – matt_Vera Dec 8 '16 at 3:45

I think another good way is via Laplace transformation. Let's denote by $L_f(s)$ the Laplace transform of $f$ in $s \in \mathbb{C}$. We have $y''(x)+y'(x)+y(x)=\frac{1}{4}$ therefore by applying the Laplace transform on both sides

\begin{align} L_{y''+y'+y}(s)&=L_\frac{1}{4} (s) \\ \Leftrightarrow L_{y''}(s)+L_{y'}(s)+L_y(s)&=\frac{1}{4} L_1(s)=\frac{1}{4s} \end{align}

where we used that $L_1(s)=\frac{1}{s}$. Additionally there are these useful properties of Laplace transforms: \begin{align} L_{y'}&=sL_y(s)-y(0)&&=sL_y(s)-3 \\ L_{y''}&=s^2L_y(s)-sy(0)-y'(0)&&=s^2L_y(s)-3s-7 \end{align}

So we get by plugging in:

\begin{align} s^2L_y(s)-3s-7+sL_y(s)-3+L_y(s)&=\frac{1}{4s} \\ \Leftrightarrow (s^2+s+1) L_y(s)&=\frac{1}{4s}+3s+10 \\ \Leftrightarrow L_y(s)&=\frac{12s^2+40s+1}{4s(s^2+s+1)}=\frac{1}{4s}+\frac{39}{4(s^2+s+1)}+\frac{11s}{4(s^2+s+1)} \end{align}

Now is the critical step that is not always so easy. We have to apply the inverse Laplace transform. Essentially we have to compute functions $f,g$ such that $L_f(s)=\frac{39}{4(s^2+s+1)}$ and $L_g(s)=\frac{11s}{4(s^2+s+1)}$.

Then by the theorem of Lerch you get $y(x)=\frac{1}{4}+f(x)+g(x)$ as the solution of your ODE. Computing $f,g$ explicitly you get $f(x)=\frac{67}{4 \sqrt{3}} e^{-x/2} \sin\left(\frac{\sqrt{3} x}{2}\right)$ and $g(x)=\frac{11}{4} e^{-x/2} \cos\left(\frac{\sqrt{3} x}{2}\right)$

You can also solve this with variation of parameters which is pretty standard but I think this is gonna be pretty nasty with computations. Computing the Wronskians etc. You can have a look at this link to get an idea how to do this in you case: https://en.wikipedia.org/wiki/Variation_of_parameters#General_second_order_equation

If you want to check: I got for the homogeneous part $$y_h(x)=Ae^{-x/2} \cos\left(\frac{x\sqrt{3}}{2}\right)+Be^{-x/2}\sin\left(\frac{x\sqrt{3}}{2}\right)$$ (where $A$ and $B$ are to be determined with the initial values) and the particular solution $$y_p(x)=\frac{1}{4}.$$ Now you get $y(x)=y_h(x)+y_p(x)$ as the solution to your ODE.


You need to add particular and general homogeneous solution before computing the coefficients from the eigenvalues. $$ y(x)=\frac14+e^{-x/2}\left(A\cos(\frac {\sqrt{3}}{2}x)+B\sin(\frac {\sqrt{3}}{2}x)\right) \\ 3=y(0)=\frac14+A $$ which gives $A=\frac{11}4$. For the derivative one gets $$ y'(x)=e^{-x/2}\left((\frac{\sqrt{3}}{2}B-\frac12A)\cos(\frac{\sqrt{3}}{2}x)-(\frac{\sqrt{3}}{2}A+\frac12B)\sin(\frac {\sqrt{3}}{2}x)\right)\\ 7=y'(0)=(\frac{\sqrt{3}}{2}B-\frac12A) $$ so that $\sqrt3 B=14+\frac{11}4=\frac{67}4$. Thus the numbers are even less nice.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.